Plastoquinone pool redox state and control of state transitions in Chlamydomonas reinhardtii in darkness and under illumination - Virtanen Olli; Tyystjärvi Esa (SPRINGER, 2023)
Movement of LHCII between two photosystems has been assumed to be similarly controlled by the redox state of the plastoquinone pool (PQ-pool) in plants and green algae. Here we show that the redox state of the PQ-pool of Chlamydomonas reinhardtii can be determined with HPLC and use this method to compare the light state in C. reinhardtii with the PQ-pool redox state in a number of conditions. The PQ-pool was at least moderately reduced under illumination with all tested types of visible light and oxidation was achieved only with aerobic dark treatment or with far-red light. Although dark incubations and white light forms with spectral distribution favoring one photosystem affected the redox state of PQ-pool differently, they induced similar Stt7-dependent state transitions. Thus, under illumination the dynamics of the PQ-pool and its connection with light state appears more complicated in C. reinhardtii than in plants. We suggest this to stem from the larger number of LHC-units and from less different absorption profiles of the photosystems in C. reinhardtii than in plants. The data demonstrate that the two different control mechanisms required to fulfill the dual function of state transitions in C. reinhardtii in photoprotection and in balancing light utilization are activated via different means.